PELESTARIAN TARI KETALANG PETANG DI SANGGAR SERENGKUH DAYUNG DI DESA RANTAU PANJANG KECAMATAN TABIR KABUPATEN MERANGIN PROVINSI JAMBI - Morenza, Elva Nia; Darmawati, Darmawati; Desfiarni, Desfiarni (FBS Universitas Negeri Padang, 2019)
AbstractThis article aimsed to reveal and describe the preservation of Ketalang Petang Dance in Rantau Panjang Village, Tabir District, Merangin District, Jambi Province. The type of this research was qualitative research with descriptive methods. The instrument of this research was the researcher herself assisted with supporting instruments such as stationeries, flash disk and photo camera. The types of data in this research were primary and secondary data. The techniques of data collection were literature studies, observation and documentation. After collecting the data, the data were analyzed according to the needs and systematically arranged related to Ketalang Petang dance preservation efforts. The results showed that the Serengkuh Dayung studio in Tabir District, Merangin Regency, Jambi Province, was still teaching and preserving the Ketalang Petang dance. Preservation efforts were carried out by Serengkuh Dayung Studio through the development and spreading. Preservation efforts by developing and spreading namely 1) adding motion, 2) adding traditional musical instruments, 3) modifying costumes, 4) developing floor patterns, levels, and group composition. In addition, the spreading was also carried out through shows.Keywords: Preservation, Ketalang Petang Dance, Serengkuh Dayung Studio